Impact of anti-Tumour Necrosis Factor (Anti-TNF) Biological Therapy on Insulin Sensitivity in Patients with Crohn's Disease: A Literature Review (Research, Society and Development, 2024)
Introduction: Crohn's disease is an inflammatory bowel disease that affects any part of the gastrointestinal tract, from the mouth to the anus, resulting in an exacerbated inflammatory process. Medication-based approaches have been effective in symptom control, and among them, biological therapy serves as an ally in maintaining patient remission. Objective: To report the action of anti-TNF biological treatment on insulin profiles in patients with Crohn's disease, considering that insulin sensitivity is impaired by the high expression of TNF-alpha in the disease. Methods: A narrative review was conducted, collecting articles from the last 10 years to seek current scientific evidence on the topic. Six steps were followed for this review, utilizing the following databases: Google Scholar, LILACS, National Library of Medicine (PubMed), and SciELO. The final number of articles was determined through a thematic similarity analysis, considering the research objective. Results: After the searches, 125 articles were identified, but only 55 articles were selected for analysis and discussion. The literature review demonstrates that insulin resistance may be higher in obese patients at risk of developing type 2 diabetes. Conclusion: In summary, it is shown that there is a relationship between metabolic diseases and inflammatory bowel disease, and anti-TNF biological therapy may be effective in both situations.